EVALUATION OF HYPERTENSION AWARENESS AMONG GENERAL POPULATION IN BAHAWALPUR, PAKISTAN: A CROSS SECTIONAL STUDY - Shahbaz Ahmad Zakki Shahbaz; Waseem abbas; Muhammad Subhan Nazar; Ahmad Umar; Muhammad Ahtsham Tariq; Ijaz ul Haq; Muhammad Junaid (International Journal of Pharmacy & Integrated Health Sciences)
Background: Globally, hypertension is one of the five major causes of death and has been identified as a serious public health issue. Hypertension therapy depends on patients' education, attitude, and awareness. The amount of public knowledge affects health policy. Still, there is lack of awareness about hypertension among the general population. Objectives: This research was conducted to assess the prevalence and awareness of hypertension (HTN) in the Bahawalpur region. Methodology: A descriptive Cross-sectional study was performed among the general population in   Bahawalpur with a self-structured questionnaire from March to June 2017. The questionnaire consisted of 35-questions, covering sociodemographic characteristics, disease awareness, disease management and prevention. Convenience sampling method was used. Descriptive and inferential statistics were applied using the IBM SPSS version 20. Results: This survey had 420 respondents in total, for a response rate of nearly 88%. Participants' average age was 26.04 years and their standard deviation was 9.605 years. The majority of participants were female (49.1%). Only three individuals achieved a score of 20 and the mean score was 13.90 ± 2.803 out of 20. Mann-Whitney and Kruskal-Wallis Males considerably outperformed females in the U-test for hypertension awareness (p>0.05). Additionally, living in an urban area, having better education, and having a higher socioeconomic level were all strongly linked to greater awareness of hypertension. Conclusion: These results showed urgent need for healthcare practitioners to pay attention to hypertension awareness campaigns. to reduce the anticipated prevalence of hypertension, researchers and policymakers must take necessary action.